Mentoring for motivation: supporting student teachers’ basic psychological needs in Chinese public kindergarten internships - Yang, Yan; Chen, Yingxin (Frontiers in Psychology, 2025)
This qualitative case study investigates how early childhood student teachers experience and interpret mentor support for their psychological needs of autonomy, competence, and relatedness during teaching internships in Chinese public kindergartens. Guided by self-determination theory, data were collected through semi-structured interviews with nine senior student teachers and analyzed using thematic analysis. The findings revealed that mentors foster student teachers’ psychological needs satisfaction through the following three key mechanisms: progressive autonomy fulfillment through selective empowerment, delegated instructional responsibility and personalized work assignment, gradual competence development via constructive feedback and optimal challenge in scaffolded tasks, and dual relatedness construction through professional collaboration and emotional care. The mechanisms enhance student teachers’ intrinsic motivation, engagement and professional identity formation. The study proposes the Developmentally Responsive Mentoring for Motivation (DRMM) model, which conceptualizes mentoring as a calibrated process of assessing readiness, assigning optimally challenging tasks, analyzing performance, and adjusting guidance, ensuring that support remains responsive to developmental and contextual needs. The model extends the applicability of self-determination theory and offers a transferable framework for teacher education programs.